PENDIDIKAN KARAKTER SISWA MELALUI PEMBELAJARAN DARING: STUDI KASUS ERA PANDEMI COVID-19 DI SMP LABORATORIUM UNIVERSITAS NEGERI MALANG - Bima Wahyu Pratama; Neni Wahyuningtyas; Nurul Ratnawati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
COVID-19 has spread all over the world and made all human activities limited. Social distance has been applied as a precaution against virus contagion and also applied in the learning activities. Online learning is applied as a learning method during the pandemic, but there are some obstacles occurred like a low ability to supervise and observe students’ progress when teachers conveyed character building for students. The research in this article is to analyze teachers’ strategies to apply character building through online learning methods and analyze teachers’ outcomes measurement to evaluate students’ character improvement. The research used a descriptive qualitative method with a study case design. The result showed that teachers’ strategies to apply character building through online learning methods are (1) using virtual communication media, (2) giving good examples or becoming a good role model for students, (3) doing intensive training and adaptation, and (4) maximizing the synergy between parents and teachers. Teachers’ outcome measurement to evaluate students’ character improvement could be seen from (1) the observation by the learning subject teachers and homeroom teachers and (2) students’ kindness reports from school counsellors and the school rules department. A recommendation for the next researcher is about the improvement of students’ character after implementing online learning at schools.